Physiological properties of cerebellar circuits in a mouse model for Angelman Syndrome and modulation of inhibitory transmission by NMDA receptor activation in the mouse hippocampus - Xue, Jiu Gang (2013)
UBE3A encodes the ubiquitin ligase E6-AP and the point mutation of this gene causes severe neurological disorder called Angelman Syndrome (AS) in a young child. To elucidate the molecular basis of AS pathogenesis and promote the design of rational therapies for AS patient, an Ube3a null mutation mouse, which recapitulated the development and behavioural defects of human patients, was generated. The mice with maternal deficiency (m-/p+) for Ube3a display several features of AS, including microcephaly, motor dysfunction, inducible seizures, abnormal hippocampal EEG and deficits in context-dependent learning. Based on the knowledge of altered UBE3A expression profile and uncoordinated movement observed in AS patients, I hypothesized that the normal function and electrophysiological properties of Purkinje neurons (PNs), which provide the sole output of cerebellar cortex might be affected by the deletion of E6-AP. The electrophysiological studies on PNs of AS mouse would be able to provide meaningful information on deciphering the molecular basis for the learning and memory deficit in AS and be helpful for developing effective drugs.